A Constituição Federal de 1988 sob a ótica da teoria comunicacional do direito: o cidadão como destinatário do texto constitucional e a linguagem técnica do direito como potencial fonte de ruídos na comunicação constitucional - Mukai, Ana Cândida de Mello Carvalho (2011)
The goal of the present research was to summarize the main ideas of the Communicational Theory of Law, whose most relevant author nowadays is Gregorio Robles, applying such theory to the reality of the Brazilian Legal System. By overseeing Law as a communicational system, it was possible to affirm that the text of the Brazilian Federal Constitution is a message to be communicated to various addressees (for example judges, prosecutors, lawyers), amongst which is the common citizen, characterized as such due its lack of knowledge concerning the technical legal language. Considering that communication depends on the concurrence of at least six elements in order to be completed (Roman Jakobson), and that the Constitution is also addressed to the common citizens, the research questioned whether the presence of the technical legal language in the constitutional text could be understood as a factor of potential noise in this communication (noise as any interference capable of disturbing the reception of the message by its addressee). The research was illustrated with three examples of terms that are typical of the technical legal language, identified in the text of the Brazilian Federal Constitution in force as potential cause of noise in the constitutional communication and, consequently, capable of rendering difficult or impeding the communication of the constitutional rights and duties to the majority of its addressees. At the end, the study discussed whether the technical legal language, as a potential source of communicational noise, could have an impact on the effectiveness or materialization of the constitutional rights and duties